2023
DOI: 10.59413/eajf/v1.i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cost of Capital on Firm Performance in Kenya

Scolar Nyamori Ochoki,
Hermans Ochieng Oloo,
Peter Mwadime Mwabaka
et al.

Abstract: This paper discusses the importance of the cost of capital and its impact on the performance of firms in Kenya. The cost of capital is affected by various factors such as interest rates, inflation, market conditions, and government policies. Financial managers use discounting cash flow techniques to evaluate capital investments, which requires the estimation of the project's cash flows and the discount rate. The article also explores the concept of capital structure and its significance in determining the cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…These findings are consistent with the theoretical framework suggesting that excessively high levels of debt can lead to higher financial risks, especially within the context of the startup industry, which often operates in uncertain environments. Previous studies have also indicated that startups burdened with debt are at a greater risk of financial difficulties and facing higher failure probabilities (Ferriswara et al, 2022;Tunji et al, 2022;Ochoki et al, 2023). Therefore, a practical recommendation emerging from these findings is that startup management in Indonesia must carefully consider their capital structure.…”
Section: Conceptual Framework N Discussionmentioning
confidence: 97%
“…These findings are consistent with the theoretical framework suggesting that excessively high levels of debt can lead to higher financial risks, especially within the context of the startup industry, which often operates in uncertain environments. Previous studies have also indicated that startups burdened with debt are at a greater risk of financial difficulties and facing higher failure probabilities (Ferriswara et al, 2022;Tunji et al, 2022;Ochoki et al, 2023). Therefore, a practical recommendation emerging from these findings is that startup management in Indonesia must carefully consider their capital structure.…”
Section: Conceptual Framework N Discussionmentioning
confidence: 97%
“…Firms are required to assess their cost of capital and contemplate measures to reduce it, such as enhancing creditworthiness or examining alternative means of financing (Ochoki et al, 2023). The process of budgeting and overseeing costs necessitates the implementation of risk planning.…”
Section: Budgetingmentioning
confidence: 99%
“…It should be noted that the involvement of current owners the process of acquiring additional capital financing is of paramount importance. This involvement may facilitate the attainment of the desired ratio of equity and debt financing, thereby contributing to the overall profitability of the firm (Ochoki et al, 2023).…”
Section: Profitabilitymentioning
confidence: 99%